The impact of the regulatory distance index of non-tariff measures on agri-food in APEC countries - Nor Surayya Abdul Samad; Tamat Sarmidi; Md Shafiin Shukor; Muhamad Rias K V Zainuddin; Norlin Khalid (Penerbit Universiti Kebangsaan Malaysia, 2025)
The agriculture sector is increasingly subject to trade barriers that affect its global supply chain. This study examines the intricate relationship between non-tariff measures (NTMs) and trade in the agricultural and food products through various models, including pooled, fixed effects, random effects, and the Poisson Pseudo-Maximum Likelihood model. The study emphasized that economic strength, in both exporting and importing countries, significantly influences the export of agri-food products. Geographic distance is a consistent trade barrier, highlighting the significance of proximity in international trade. The impact of exchange rates is multifaceted differing across models. The regulatory distance index of NTMs presents varying impacts, with positive and negative coefficient becoming more pronounced through entity-specific factors. Since NTMs are increasingly shaping global trade, particularly in the Asia-Pacific Economic Cooperation (APEC), these complex relationships need better understanding to minimize trade barriers and promote growth in the sector. The study offers valuable insights for policymakers, industry players, and researchers, underlining the importance of addressing NTMs towards formulating harmonized regulatory standards to boost trade and economic growth. Future researcher should explore the evolving dynamics of NTMs in the global trade landscape.